Geographical and ecological analyses of multiple myeloma in Denmark: Identification of potential hotspot areas and impact of urbanisation. (4th December 2022) - Bertelsen, Lise Dueholm; Børty Nielsen, Lars; Christensen, Heidi Søgaard; Bøgsted, Martin; Gregersen, Henrik; Pedersen, Robert Schou; Klostergaard, Anja; Schnack, Brian Iversen; Pedersen, Per Trøllund; Abildgaard, Niels; Hermansen, Emil; Vangsted, Annette Juul; et al.
Abstract: Background: The aetiology of multiple myeloma (MM) is unknown but various environmental exposures are suspected as risk factors. We present the first paper analysing the geographical distribution of MM in Denmark at the municipal level to investigate variations that could be explained by environmental exposures. Methods: Patients diagnosed with MM in Denmark during 2005–2020 were identified from nationwide registries and grouped into the 98 Danish municipalities based on residence. The age‐ and sex‐standardised incidence rate (SIR) of each municipality was compared to the national incidence in a funnel plot with 95% control limits. Differences in SIRs of rural, suburban, and urban areas were evaluated with incidence rate ratios. Results: In total, 5243 MM patients were included. Overall, we found a heterogeneous geographical distribution of MM and a potential hotspot in southern Denmark. This hotspot contains three municipalities with SIRs above the 95% control limit assuming considerably higher rate of MM compared to the national incidence rate. A significant higher SIR was found in rural areas compared to urban areas. Conclusion: The geographical distribution of MM in Denmark indicates that the risk of developing MM depends on place of residence probably due to environmental factors.